Accountability of Village Fund Management as Corruption Prevention Management of Village Fund Management - Ash-shidiqqi, Ellectrananda; Wibisono, Hindrawan (Law Research Review Quarterly, 2018)
The use of Village Funds has not been used optimally for village development. Some cases of misappropriation of village funds occur because of the lack of accountability in the use of village funds and the lack of supervision from relevant parties. The incompetence of the use of village funds is also the cause of cases of misuse and corruption of village funds. This research focuses on aspects of accountability and supervision of village funds using literature. The results of this study produce an ideal model of accountability for the use of village funds ranging from supervision to use so that the village is expected to be more leverage in using village funds for development.